WNT/?-CATENIN PATHWAY IS AFFECTED IN PRIMARY SJOGREN'S SYNDROME - Omercikoglu, Z.; Karatas, A.; Catak, O.; Oz, B.; Erman, F.; Şahin, Kazım; Koca, S. S. (Bmj Publishing Group, 2017)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 14-17, 2017 -- Madrid, SPAIN